Dimension of halal purchase intention: A preliminary study - Shaari, J.A.N.; Mohd Arifin, N.S. (2009)
This paper aims to do preliminarily study on dimensions within factors associated to Halal purchase intention. Using questionnaire surveys on 135 respondents from Kota Samarahan District in Sarawak, Malaysia, 9 dimensions named Solidity, Certainty, Universal, Brand Association, Purity, Conformity, Halal-ness, Place & Distribution, and Knowledge were extracted using Varimax Factor Analysis from four suggested variables: Marketing Concept; Awareness, Halal Certificate ; and Religiousity. The paper intends to path the way for deeper and more thorough future research on the area.